Wnt/β‐catenin signaling and adipogenic genes are associated with intramuscular fat content in the longissimus dorsi muscle of Korean cattle. (7th June 2013) - Jeong, J. Y.; Kim, J. S.; Nguyen, T. H.; Lee, H. ‐J.; Baik, M.
Summary: Intramuscular fat (IMF) is an important trait that influences beef quality. In two studies, we examined the possible involvement of the Wnt/β‐catenin signaling pathway in IMF deposition in Korean cattle. In study 1, using a group of bulls and steers, we found that castration, a non‐genetic factor, decreased ( P  < 0.01) the expression of both the WNT10B and CTNNB1 genes, whereas it increased the expression of the Wnt antagonist secreted frizzled‐related proteins 4 ( SFRP4, P  < 0.001) and the adipogenic CCAAT/enhancer binding protein (C/EPB), alpha ( CEBPA, P  < 0.001) and peroxisome proliferator‐activated receptor gamma ( PPARG, P  < 0.05) genes in longissimus dorsi muscle (LM) tissue. The WNT10B and CTNNB1 mRNA levels showed strong ( P  < 0.001) negative correlations ( r  = −0.68 and r  = −0.73 respectively) with the IMF content, whereas the SFRP4, CEBPA and PPARG mRNA levels showed strong ( P  < 0.01) positive correlations ( r  = 0.70, 0.70 and 0.64 respectively) with the IMF content. Large variation still exists in the IMF content of steers, implying that genetic factors affect IMF deposition. Using a different group of steers, a correlation analysis in study 2 also showed that the expression of the WNT10B and CTNNB1 genes, and SFRP4 and adipogenic genes was negatively and positively associated with the IMF content respectively. Our findings suggest that downregulation of the Wnt/β‐catenin signaling pathway genes, but upregulation of Wnt antagonist SFRP4 and adipogenic gene expression following castration, contributes to increased IMF deposition in the LM. Our results demonstrate that both non‐genetic factors (castration) and genetic variation within the steer group affect the gene expression pattern of the Wnt/β‐catenin signaling pathway.